Port Mackenzie, Alaska - Deep Soil Compaction, Spin Fin- Pile Tension Test And Dock Construction - Garth Howlett (Deep Foundations Institute, 2006)
In 1998 the Matanuska-Susitna Borough formed the new port district at Point MacKenzie, known as Port MacKenzie, located directly across the Knik Arm from Anchorage. In 1991 PND Engineers Inc. (PND), working with the Matanuska-Susitna Borough manager and port director, envisioned a fill structure at Port MacKenzie with a 500-foot-long Open Cell? sheet-pile bulkhead face extending to EL -20 feet Mean Lower Low Water (MLLW) at the face. Now under operation the fill created 5.5 acres of tideland property using local materials for fill. The fill is protected from 2- to-3 foot-thick ice pans and 9 feet per second (fps) tidal currents by an envelope of armor rock. Construction required working in water with 30 to 40 feet of tidal variation. Construction required placement of frozen fill in water depths possibly exceeding 50 feet, creating real concerns about soil consolidation and long-term maintenance issues. A plan was prepared to consolidate the soils using Vibracompaction. Soil Density and consolidation were monitored during the work. In 2003 the port district and NPI, a wood chip export company, formalized an agreement to construct a deep water port facility at Port MacKenzie for cape-class bulk carriers. PND provided planning, studies, geotechnical investigation, design documents and construction inspection for a 500-foot-long trestle with a platform dockhead and dolphins providing 1,100 feet of dock face in EL -70 MLLW as shown in Figure 1. Design included installation of large-diameter spin-fin piles driven on a 2V:1H batter. Also included was a 300-ton tension test of smaller spin-fin piles.